THE SNAKES AND LADDERS GAME CAN HELP CHILDREN'S COGNITIVE DEVELOPMENT IN THE EARLY YEARS - Nur Azizah; Eka Damayanti; Umi Kusyairy (International Conferences on Early Childhood Education Proceedings, 2023)
This study aims to determine the increase in cognitive development before and after being given a game of snakes and ladders to group B students at RA Perwadina Tokka, Alehanue Village, Sinjai Regency. This research is descriptive quantitative research. The population of this study was group B which consisted of 21 children consisting of 12 girls and 9 boys. The sample in this study was 10 children consisting of 5 girls and 5 boys. This research instrument uses observation and documentation guidelines. The data analysis technique used is descriptive statistics. The results showed that there was an increase in cognitive development in group B children in RA Perwanida Tokka as evidenced by the value after playing the Snakes and Ladders Game which was 21.1 higher before playing the Snakes and Ladders Game which was 13.9 with a difference of 7.2. It can be concluded that there is an increase in cognitive development through Snakes and Ladders Games for students. The research implies that the use of Snakes and Ladders Games can be used to improve cognitive development in students. Therefore this research can be used as a consideration and reference for the community, especially parents and educators at RA Perwanida Tokka, Alehanuae Village to improve cognitive development through the Snakes and Ladders Game.